Composition of Functional Bacteria on Suppressive and Conducive Soil for Fusarium Wilt on Chilli - Amara, Khansa; Giyanto; Widodo; Sudiana, I Made (Jurnal Fitopatologi Indonesia, 2023)
Composition of Functional Bacteria on Suppressive and Conducive Soil for Fusarium Wilt on Chilli The phenomenon of suppressive soil has been widely studied to control plant diseases in the field. Suppresive soil is characterized by its contain of functional microbes that can suppress pathogen populations. This study aims to determine and compare the composition of functional bacteria on suppressive and conducive soil of fusarium wilt. The research method consists of soil sampling in the field, isolation of functional bacteria from suppressive soil (SS) and conducive soil (CS) samples, calculation of bacterial population and type, biosafety screening, and characterization of functional bacteria in suppressing of Fusarium oxysporum. The results showed that the bacterial population in SS was higher than those in CS, especially for heat-tolerant bacteria and the fluorescent Pseudomonads. The high population of bacteria is supported by the high value of functional bacterial diversity in SS (H’ 3.70 > 3) compared to CS, which is classified as medium (1 < H’ 2.07 < 3), with the distribution of functional bacteria classified as almost evenly distributed and no dominance of certain types in SS and CS. The percentage of nonpathogenic bacteria in SS is higher than in CS, i.e. 51% and 23%, respectively. These bacteria have potential as plant growth promoting bacteria (PGPB) by producing IAA or dissolving phosphate alone of 24% and 10%, respectively in suppressive soils; and of 14% and 29%, respectively in conducive soils. Only bacteria derived from suppressive soils were able to produce IAA while dissolving phosphate with a percentage of as much as 48%.